Ventriculitis due to multidrug-resistant gram-negative bacilli associated with external ventricular drain: evolution, treatment, and outcomes - Corona-Nakamura, Ana Luisa; Arias-Merino, Martha Judith; Ávila-Esparza, Eleazar Iván; Tolentino-Corona, María de Lourdes; Cañedo-Castañeda, César Cuauhtémoc; Flores-Salinas, Héctor Enrique; Corona-Macías, Juan Fernando; Vázquez-Arias, Martha Elena (Frontiers in Neurology, 2024)
Introduction Nosocomial infectious ventriculitis caused by multidrug-resistant (MDR) Gram-negative bacilli associated with external ventricular drainage (EVD) placement poses a significant mortality burden and hospital costs. Objectives This study aims to analyze the characteristics, ventriculitis evolution, treatment, and outcomes of patients with ventriculitis due to MDR Gram-negative bacilli associated with EVD placement. Methods A retrospective cohort study focusing on patients with nosocomial infection caused by MDR Gram-negative bacilli while on EVD was conducted from 2019 to 2022. Medical, laboratory, and microbiological records were collected. The antibiotic resistance of the Gram-negative bacilli isolated in the cerebrospinal fluid (CSF) of patients was analyzed. The risk factors were identified using univariate risk models and were analyzed using survival curves (Cox regression). An adjusted Cox proportional hazards model was also constructed. Results Among 530 patients with suspected EVD-associated ventriculitis, 64 patients with isolation of Gram-negative bacilli in CSF were included. The estimated mortality was 78.12%. Hemorrhages (intracranial, subarachnoid, and intraventricular) were observed in 69.8% of patients. Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa were the most frequently isolated bacilli. In the univariate analysis, significant risk factors for mortality included arterial hypertension, a Glasgow Coma Scale (GCS) score of ≤ 8, invasive mechanical ventilation (IMV) upon hospital admission and during hospitalization, septic shock, and ineffective treatment. The adjusted Cox proportional hazards model revealed that septic shock (HR = 3.3, 95% CI = 1.5–7.2; p = 0.003) and ineffective treatment (HR = 3.2, 1.6–6.5, 0.001) were significant predictors. A high resistance to carbapenems was found for A. baumannii (91.3%) and P. aeruginosa (80.0%). Low resistance to colistin was found for A. baumannii (4.8%) and P. aeruginosa (12.5%). Conclusion Ineffective treatment was an independent hazard factor for death in patients with ventriculitis caused by MDR Gram-negative bacilli associated with EVD.